The Role of CDR1as in Proliferation and Differentiation of Human Umbilical Cord-Derived Mesenchymal Stem Cells - Lunyu Yang; Zhang Bin; Shi Hui; Li Rong; Benshuai You; Peipei Wu; Xinye Han; Hui Qian; Wenrong Xu (Stem Cells International)
Mesenchymal stem cells derived from human umbilical cord (hucMSCs) are considered a promising tool for regenerative medicine. circRNAs as newly discovered noncoding RNAs are involved in multiple biological processes. However, little has been known about the function of circRNAs in the proliferation and differentiation of hucMSCs. In this study, we selected several circRNAs expressed in MSCs from circBase and found that CDR1as expression level was markedly significant. We observed that, compared with that of uninduced hucMSCs, the CDR1as expression level of induced hucMSCs decreased with cell induction differentiation. By using siRNA to knock down CDR1as of hucMSCs, we discovered that proliferation was inhibited but the apoptosis increased. In addition, we found that the expression of stemness transcription factors (STFs) was downregulated after CDR1as knockdown and the adipogenesis and osteogenesis potential of hucMSCs was impaired. Our findings suggest that CDR1as takes a part in maintaining proliferation and differentiation of hucMSCs, providing clues for MSC modification and further for stem cell therapy and tissue regeneration.